Antioxidant Activity and Body Scrub Formulation from Yellow Dragon Fruit Peel (Selenicereus megalanthus) Extract. - Yoga Wardana, Fendi; Islamiyah, Tufa Nur; Arifin, Irnandhea Putri (BORNEO JOURNAL OF PHARMASCIENTECH, 2025)
Antioxidant agents are substances that repress oxidation responses due to free radicals which can cause harm to unsaturated greasy acids in cell divider films, blood vessel cells and lipid tissue. Dragon fruit has been reported to have high antioxidant activity. The aim of the research was to determine the antioxidants in yellow dragon fruit peel (Selenicereus megalanthus) extract and formulate them as body scrub. Research design of laboratory experiments, the yellow dragon fruit peel was extracted by maceration using 96% ethanol. Antioxidant activity testing was carried out using 2,2-diphenyl-1-picrylhydrazyl (DPPH). Preparation of the formula using extract concentration variations of 1% and 3%. The evaluation of body scrub preparation include homogeneity, organoleptic, pH and dispersive power. The yellow dragon fruit peel extract showed antioxidant activity with IC50 value of 2.7 ppm (strong antioxidant). The results of the evaluation of the two formulas did not provide a significant difference. Both body scrub preparations were homogeneous, organoleptic evaluation showed a yellowish-white color and does not become rancid, pH range of 7.7-7.8 and dispersive power range of 4.3-4.4 cm. The yellow dragon fruit peel extract has very strong antioxidant activity and can be formulated as a scrub product.